Nerve Cases : High Yield Scenarios for Oral and Written Testing - Hanna, Amgad S. (Springer International Publishing : Imprint: Springer, 2017)
This book addresses the severe knowledge deficit in peripheral nerve amongst neurosurgeons, however this topic represents an integral part of the oral board examination. The book employs a case based approach with the highest-yield scenarios for oral boards, primarily focusing on nerve entrapments, trauma and tumors. Thanks to its question and answer format, the reader is encouraged to think about the cases and questions as if taking the real exam before they check the answers. The work also includes common pitfalls, a section on nerve examinations including video recordings, and a section on important clinical findings that should be diagnosed from the picture. The book not only serves neurosurgeons, but also plastic surgeons, orthopedists, and neurologists.
Keywords: Medicine.; Neurosurgery.; Orthopedics.; Plastic surgery.; elektronické knihy; electronic books